Living radical polymerization of vinyl acetate mediated by iron(iii) acetylacetonate in the presence of a reducing agent. Issue 117 (10th November 2015) - Wang, Jirong; Zhou, Jun; Sharif, Hussameddin S. E. M.; He, Dan; Ye, Yun Sheng; Xue, Zhigang; Xie, Xiaolin
Abstract : The Fe(acac)3 -mediated OMRPs of VAc in the presence of a reducing agent were reported. Abstract : Iron(iii ) acetylacetonate (Fe(acac)3 ) was employed to mediate the controlled radical polymerization of vinyl acetate (VAc) in the presence of a reducing agent (RA). Polymerizations were conducted with a molar ratio of [VAc]0 /[initiator]0 /[Fe(acac)3 ]0 /[RA]0 /[ligand]0 = 500 : 0.8 : 1 : 2 : 3 and a volume ratio of VAc/solvent = 1 at 70 °C to investigate the effects of initiator, solvent, and reducing agent on the polymerization reaction. The kinetic plots of VAc polymerizations were linear, and the molecular weights ( M n ) increased proportionately with monomer conversions.